Effectiveness of Agricultural Information Disseminated Through Mobile Apps and Social Media - Madhushekar, B. Raja; Rani, V. Sudha; Padmaveni, C.; Reddy, M. Malla; Kumar, B. Anil (International Journal of Bio-resource and Stress Management, 2024)
The present investigation was conducted during June, 2021 to February, 2022 in twelve villages under DAATTC, six each in Bhuvanagiri and Jangaon districts, Telangana, India on the use of social media as a source of agricultural information, use pattern, preference, purpose, ranking of different social media used, information processing and its effectiveness among farmers. Social media emerged as highly powerful tools in facilitating online social interactions and has shown tremendous potential in facilitating information exchange among individuals. These tools are meant for digital communication helping in interaction among a group of people. The data were collected from farmers of Bhuvanagiri and Jangaon districts, with a sample size of 120 respondents through a structured interview schedule. 84.16% of the farmers used social media platforms for getting agriculture related information, the most preferred social media were WhatsApp, Youtube and Facebook. Garrett ranking analysis revealed that information seeking was the most preferred purpose of social media use among farmers followed by chatting/connecting with peers and watching agricultural videos. 54.17% of the farmers preserved this information obtained from social media for future use. 45.00% of them discussed this information with progressive farmers and 42.50% of them discussed with friends. 72.50% of the respondents had enhanced knowledge about pest and diseases. The personal variable of the respondents’ such as education, farm-size, scientific orientation, social participation, income, innovativeness and information seeking behaviour were significant and positively correlated (at 0.01% level of probability) with social media use.